Eyebrow lift with cosmetic procedures: how to approach it - Rebecca Ignacio Subirá Medina; Gladstone Eustáquio de Lima Faria;; Ricardo Frota Boggio (Surgical & Cosmetic Dermatology)
Eyebrow ptosis presents a significant challenge for cosmetic professionals. Minimally invasive procedures can improve eyebrow positioning; however, a thorough understanding of its varied etiologies is essential. The primary causes include skin laxity, muscular dysfunction, and tissue deflation, with the latter subdivided into frontal, temporal, and superciliary deflation. A precise diagnosis allows for the appropriate indication of microfocused ultrasound, botulinum toxin, biostimulators, and hyaluronic acid-based fillers, either as standalone treatments or in combination. At the end of this review, a treatment algorithm for eyebrow ptosis is proposed.